Maternal breast cancer and communicating with children: A qualitative exploration of what resources mothers want and what health professionals provide. (23rd August 2019) - Sinclair, Michelle; Schofield, Penelope; Turner, Jane; Rauch, Paula; Wakefield, Claire; Mann, G. Bruce; Newman, Louise; Mason, Kylie; Gilham, Leslie; Cannell, Julia; Stafford, Lesley
Abstract: Objective: To explore the communication and resource needs of mothers diagnosed with breast cancer treated with curative intent in communicating with their young children and to identify gaps in the resources and support provided to these women. Methods: Data were collected via semi‐structured telephone interviews from 13 mothers who were diagnosed with breast cancer while parenting a young child (age 3–12 years), and 10 health professionals in Victoria, Australia. Data were analysed qualitatively using the Framework Method. Results and Conclusion: Mothers and health professionals prioritised communication with children about the cancer diagnosis; however, health professionals and mothers differed in their views of parents' communication needs both in terms of the nature of the support/information needed and the delivery of this support/information. Mothers wanted easily accessible resources that were both instructive and practical. Mothers also emphasised quality over quantity of support. Health professionals were mostly aware of mothers' needs, however, emphasised less instructive support and information. This study highlights the need for improved coordination and tailoring of psychosocial resources and supports for these parents and families communicating about a cancer diagnosis with their young children.